Pengembangan Teknologi Digital Terhadap Pemenuhan Keselamatan Konstruksi dI Indonesia - Putriwardani, Liza; Susilawati, Susilawati (Alahyan Jurnal Pengabdian Masyarakat Multidisiplin, 2024)
It is well known that digital development is happening at a breakneck pace nowadays, which can greatly facilitate and improve the efficiency of construction operations. Apart from its advantages, advances in digital technology have also impacted the construction industry, as demonstrated by its ability to ensure construction safety. In implementing SMKK, it must adhere to Security, Safety, Health, and Sustainability Standards per PUPR Minister Regulation Number 10 of 2021. Public safety, environmental protection, occupational health and safety, and construction engineering safety are all guaranteed if these criteria are met. This study will discuss technical advances made possible by the implementation of Construction Safety, by utilizing the contents of existing SMKK and K4 Standards. Based on this, information collected through scientific journals about building projects in Indonesia continues